Lexical and grammatical features of antonyms in artistic style(Example of Alexandre Dumas's novel "20 years later" (20 ans après)) - Mustofoqulov Farhod Xolmurod o’g’li (Genius Journals, 2022)
This article analyzes the use of French antonyms in an artistic style and its lexical and grammatical features in the novel "20 years after" (20 ans après) by the famous French writer Alexandre Dumas.
Keywords: artistic coloring; antonymy; synonymy; lexeme